Adhesion molecule L1 inhibition increases infarct size in cerebral ischemia-reperfusion without change in blood-brain barrier disruption. (2nd September 2021) - Chi, Oak Z.; Theis, Thomas; Kumar, Suneel; Chiricolo, Antonio; Liu, Xia; Farooq, Saad; Trivedi, Nishta; Young, Wise; Schachner, Melitta; Weiss, Harvey R.
ABSTRACT: Objective: Neural cell adhesion molecule L1CAM (L1) is involved in neuroprotection. To investigate a possible neuroprotective effect of L1 during ischemia, we determined whether blocking L1 with an antagonistic antibody would worsen the outcome of focal cerebral ischemia-reperfusion and increase blood-brain barrier (BBB) disruption. Methods: Transient middle cerebral artery occlusion (MCAO) was performed in anesthetized rats. Five µg of antagonistic mouse IgG monoclonal L1 antibody 324 or non-immune control mouse IgG was applied on the ischemic-reperfused cortex during one hour of MCAO and two hours of reperfusion. At two hours of reperfusion, BBB permeability, size of infarct using tetrazolium staining, number of TUNEL-labeled apoptotic cells, and immunohistochemistry for expression of PTEN and p53 were studied. Results: The antagonistic L1 antibody 324 increased the percentage of cortical infarct area (+36%), but did not affect BBB permeability in the ischemic-reperfused cortex. The antagonistic L1 antibody increased number of apoptotic neurons and p53 expression, but decreased PTEN expression. Conclusion: Functional antagonism of L1 increases infarct size by increasing numbers of apoptotic neurons without affecting BBB permeability during the early stage of cerebral ischemia-reperfusion. Our data suggest that L1 affects primarily the brain parenchyma rather than BBB during early stages of cerebral ischemia-reperfusion and that endogenous brain L1 may be neuroprotective.